Tika, Pono and Aroha in three novels by Patricia Grace : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts, Massey University - Peters, Robin J (Massey University, 2000)
This thesis focuses on tika, pono and aroha. While each word is able to stand alone and has been applied to each text in this regard, when considered together they encompass a concept which in translation means doing the right thing with integrity and in love. This term which is an aspect of whanaungatanga, may be described as central to a Maori sense of self and of community. The interpretation of this concept as used in this thesis is attributed to Pa (Father) Henare Tate. His credentials are set out in the Tate Fax, Appendix 2. They include seven years of study for the priesthood and twelve years at Panguru. During his period of duties at Panguru he officiated at the burial of one hundred of the local people and a further two hundred who were brought back to their turangawaewae. His knowledge of Te Ao Maori and Te Wairua Maori (The world of Maori and the world of Spirituality) was gained by sitting at the feet of his elders at Panguru. The period of time spent with them on a continuous basis would equate to twenty-four hours a day for five years. [From Preface]
Some Maori language content.
Keywords: Tika; Pono; Aroha; Patricia Grace; Mutuwhenua; Potiki; Baby No-Eyes